2024
DOI: 10.3389/fnut.2024.1289750
|View full text |Cite
|
Sign up to set email alerts
|

Lacking P2X7-receptors protects substantia nigra dopaminergic neurons and hippocampal-related cognitive performance from the deleterious effects of high-fat diet exposure in adult male mice

Chiara Rossi,
Mariarosaria Distaso,
Francesco Raggi
et al.

Abstract: BackgroundDietary fat consumption, involved in the pathogenesis of insulin resistance and impaired glucose metabolism, is linked with decline in cognitive functions, dementia, and development of Parkinson’s disease and Alzheimer’s disease. Mature IL-1β, requiring the activation of the P2X7 receptor (P2X7R)-inflammasome complex, is an important mediator of neuroinflammation. The aim of the study was to test whether P2X7R activation might interfere with systemic and cerebral metabolic homeostasis.MethodsWe treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This is linked to a reduced expression in HFD of BDNF, which is involved in neuronal plasticity and energy metabolism [43]. The release of IL-1β, one of the most important mediators of neuroinflammation, depends on the activation of the P2X7 receptor (P2X7R)-inflammasome complex [44]. The stimulation of P2X7R, preferentially localized on microglia, increases the production of neurodegeneration-inducing molecules such as cytokines, chemokines, reactive oxygen and nitrogen species, and proteases [45].…”
Section: Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is linked to a reduced expression in HFD of BDNF, which is involved in neuronal plasticity and energy metabolism [43]. The release of IL-1β, one of the most important mediators of neuroinflammation, depends on the activation of the P2X7 receptor (P2X7R)-inflammasome complex [44]. The stimulation of P2X7R, preferentially localized on microglia, increases the production of neurodegeneration-inducing molecules such as cytokines, chemokines, reactive oxygen and nitrogen species, and proteases [45].…”
Section: Neuroinflammationmentioning
confidence: 99%
“…The stimulation of P2X7R, preferentially localized on microglia, increases the production of neurodegeneration-inducing molecules such as cytokines, chemokines, reactive oxygen and nitrogen species, and proteases [45]. Interestingly, in a novel study on mice, Rossi et al reported that the lack of P2X7R is protective against the neuronal damage induced in crucial cognitive areas by HFD exposure [44].…”
Section: Neuroinflammationmentioning
confidence: 99%